2018
DOI: 10.1063/1.5040327
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced magnetization changes in aggregated and isolated cobalt ferrite nanoparticles

Abstract: The light-induced magnetization changes in cobalt ferrite nanoparticles are reinvestigated to probe the mechanism of photomagnetic behavior and to uncover the essential criteria required to observe the effect. Irradiation with white light results in pronounced demagnetization as evidenced by a decrease in the coercivity (ΔHc ∼ 3 kOe at 10 K) and a drop in the high field magnetization at 70 kOe. Wavelength dependent studies show the optical excitation driving the effect is broad in nature. Power and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…The dark-state coercivity of 12.17 ± 0.04 kOe decreases to 9.43 ± 0.09 kOe with light and is accompanied by a reduction in the remnant and high-field-magnetization values. This behavior with light is consistent with earlier reports on cobalt ferrite nanoparticles and has been attributed to decoupling of surface spins on the nanoparticles resulting in a reduction of magnetic volume and changing interparticle interactions within the aggregates . Similar magnetization vs field plots with and without light for the core–shell-like 2 are presented in Figure .…”
supporting
confidence: 91%
See 3 more Smart Citations
“…The dark-state coercivity of 12.17 ± 0.04 kOe decreases to 9.43 ± 0.09 kOe with light and is accompanied by a reduction in the remnant and high-field-magnetization values. This behavior with light is consistent with earlier reports on cobalt ferrite nanoparticles and has been attributed to decoupling of surface spins on the nanoparticles resulting in a reduction of magnetic volume and changing interparticle interactions within the aggregates . Similar magnetization vs field plots with and without light for the core–shell-like 2 are presented in Figure .…”
supporting
confidence: 91%
“…Cobalt ferrite nanoparticles were shown by Giri et al , to undergo a light-activated decrease in coercivity. A more recent study revealed white light irradiation also decreases high-field magnetization . The light-induced demagnetization effects were attributed to decoupling of the surface spins, leading to a change in volume of the magnetically ordered domains.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The reagent concentrations reported by Pato-Doldán et al , for the solvent layering synthesis of 1 provided the starting point for the particle syntheses reported here. Although surfactants are sometimes used to isolate discrete particles of the formate networks, they were not used in the present work to avoid their impact on solid-state properties, which at the mesoscale can be altered by surface modification and with an eye toward further work incorporating the particles into heterostructures.…”
Section: Resultsmentioning
confidence: 99%